Single-Cell RNA-Seq and Bulk RNA-Seq Reveal Intratumoral Heterogeneity and Tumor Microenvironment Characteristics in Diffuse Large B-Cell Lymphoma - Zhao, Yang; Xu, Hui; Zhang, Mingzhi; Li, Ling (Frontiers in Genetics, 2022)
Background: Diffuse large B-cell lymphoma (DLBCL) is the most common histologic subtype of non-Hodgkin’s lymphoma (NHL) with highly heterogeneous genetic and phenotypic features. Therefore, a comprehensive understanding of cellular diversity and intratumoral heterogeneity is essential to elucidate the mechanisms driving DLBCL progression and to develop new therapeutic approaches. Methods: We analyzed single-cell transcriptomic data from 2 reactive lymph node tissue samples and 2 DLBCL lymph node biopsy tissue samples to explore the transcriptomic landscape of DLBCL. In addition, we constructed a prognostic model based on the genes obtained from differential analysis. Results: Based on gene expression profiles at the single cell level, we identified and characterized different subpopulations of malignant and immune cells. Malignant cells exhibited a high degree of inter-tumor heterogeneity. Tumor-infiltrating regulatory CD4+ T cells showed highly immunosuppressive properties and exhausted cytotoxic CD8+ T cells were highly expressed with markers of exhaustion. Cell communication analysis identified complex interactions between malignant cells and other cell subpopulations. In addition, the prognostic model we constructed allows for monitoring the prognosis of DLBCL patients. Conclusion: This study provides an in-depth dissection of the transcriptional features of malignant B cells and tumor microenvironment (TME) in DLBCL and provides new insights into the tumor heterogeneity of DLBCL.